$\left( L^{p} ,L^{q} \right)$ Properties of the Potential-Type Integrals Associated to Non-doubling Measures - Hajibayov, Mubariz G. (Sarajevo Journal of Mathematics, 2024)
The $\left( L^{p} ,L^{q} \right) $ boundedness of the potential-type integrals associated to non-doubling measures are investigated. 1991 Mathematics Subject Classification. 31B15, 46E35